LST8 regulates cell growth via target-of-rapamycin complex 2 (TORC2) - Wang, Tao; Edgar, Bruce (Molecular and cellular biology, 2012)
The evolutionarily conserved serine/threonine protein kinase target-of-rapamycin (TOR) controls cell growth as a core component of TOR complexes 1 (TORC1) and 2 (TORC2). Although TORC1 is the more central growth regulator, TORC2 has also been shown to affect cell growth. Here, we demonstrate that Drosophila LST8, the only conserved TOR-binding protein present in both TORC1 and TORC2, functions exclusively in TORC2 and is not required for TORC1 activity. In mutants lacking LST8, expression of TOR and RAPTOR, together with their upstream activator Rheb, was sufficient to provide TORC1 activity and stimulate cell and organ growth. Furthermore, using an lst8 knockout mutation, we show that TORC2 regulates cell growth cell autonomously. Surprisingly, however, TORC2 does not regulate cell growth via its best-characterized target, AKT. Our findings support the possible application of TORC2-specific drugs in cancer therapy.